(3acQI Yf GdceHjhJQ GdeMehd (B=s LAPTOP - (3YHO GdMGaX, eMeO cGeds; (3NdjaI, LeGds ((3GdbGgQIs (3GdOGQ GdeUQjI ddYdhes, 2008)
(3jJfGhd gPG GdcJGH GdehVhYGJ HTcd Yedi h HWQjbI LOjOI ddCNP HjO GdOGQS HCSQY hbJ eecf dJYde (BExcel 2007 (3h GMJQGag ai eOI JSYI CjGes
(3GdYGde ef MhdfG (B((3GdceHjhJQ(B)s
1
Keywords: Computer Science; (3GdMGSHGJ GdEdcJQhfjIs